2014
DOI: 10.1111/eci.12239
|View full text |Cite
|
Sign up to set email alerts
|

18F‐FDG PET/CT as a predictor of hereditary head and neck paragangliomas

Abstract: Background Hereditary head and neck paragangliomas (HNPGLs) account for at least 35% of all HNPGLs, most commonly due to germline mutations in SDHx susceptibility genes. Several studies about sympathetic paragangliomas have shown that 18F-FDG PET/CT was not only able to detect and localize tumors, but also to characterize tumors (18F-FDG uptake being linked to SDHx mutations). However, the data concerning 18FFDG uptake specifically in HNPGLs have not been addressed. The aim of this study was to evaluate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…18 F-FDG PET/CT is also useful for localizing benign PPGLs (7). Interestingly, 18 F-FDG uptake varies among PPGLs of different genotypes, with the highest standard uptake values (SUVs) being observed in SDH and VHL-related tumors (5,8). The precise mechanism behind these genotype-specific differences in 18 F-FDG uptake has not been elucidated.…”
mentioning
confidence: 99%
“…18 F-FDG PET/CT is also useful for localizing benign PPGLs (7). Interestingly, 18 F-FDG uptake varies among PPGLs of different genotypes, with the highest standard uptake values (SUVs) being observed in SDH and VHL-related tumors (5,8). The precise mechanism behind these genotype-specific differences in 18 F-FDG uptake has not been elucidated.…”
mentioning
confidence: 99%
“…123 I-MIBG scintigraphy has a sensitivity of 77-90% and specificity of 95-100% in the detection of PHEO; its sensitivity is lower for PGLs, especially for some that are hereditary (see below (Taieb et al 2009, 2014a). Several potential diagnoses should be considered in cases of highly 18 F-FDG-avid adrenal masses (Fig.…”
Section: Functional Imagingmentioning
confidence: 99%
“…Several studies have found that 18 F-FDG PET/CT is excellent for SDHx germline mutations in comparison to other tumor types, regardless of tumor location . The performance and PGLs (Blanchet et al 2014a). By using an uptake ratio, it has even been shown that models could be established for predicting PHEO/PGL genotypes (Blanchet et al 2014a Ga-DOTA peptides Figure 5 Functional imaging findings in a case of extraadrenal sympathetic SDHBrelated PGL.…”
Section: Influence Of Genotype On Imaging Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…18 The 18 F-FDG PET/CT can differentiate SDHx-related HNPGL from sporadic ones with 80% accuracy. 19 However, no such data are available in children.…”
Section: Choice Of Nuclear Imagingmentioning
confidence: 99%